External Constraints and Endogenous Growth: Why Didnt Some Countries Benefit From Capital Flows? - Karine Gente; Miguel A. León-Ledesma; Carine Nourry (University of Kent, School of Economics, 2013)
Empirical evidence on the growth benefits of capital inflows is mixed. The growth benefits accruing from capital inflows also appear to be larger for high savings countries. We explain this phenomenon using an OLG model of endogenous growth in open economies with borrowing constraints that can generate both positive and negative growth effects of capital inflows. The amount an economy can borrow is restricted by an endogenous enforcement constraint. In our setting, with physical capital and a pay-as-you-go pensions system, the steady state is unique. However, it can either be constrained or unconstrained. In a constrained economy, opening up to equity and FDI inflows can be bad for growth because it makes the domestic interest rate too low, which endogenously tightens borrowing constraints. Agents decrease savings and investment in productivity-enhancing activities resulting in lower growth. Results are reversed in an unconstrained economy. We also provide a quantitative analysis of these constraints and some policy implications.
Keywords: F43; F34; 330; overlapping generations; endogenous credit constraint; capital flows; endogenous growth